2018
DOI: 10.3390/ma11071166
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Radiative Cooling on Reducing the Temperature of Greenhouses

Abstract: Currently, greenhouses are widely used for the cultivation of various crops. However, in tropical and subtropical regions, undesired near-infrared radiation (NIR) causes heat loads inside the greenhouse. Recent works have demonstrated that radiative cooling, releasing energy via radiative heat exchange where the heat is dumped directly into outer space, can be achieved by using silica particles designed to emit in the infrared atmospheric transparency window. The purpose of this study is to improve the plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…[1,2] UV radiation affects film degradation and pollinators' behavior, and NIR radiation is a direct source of heat, which penetrates the greenhouses, excessively increasing the temperature, which is harmful to people who work inside and to the crops. [3] Thus, organic and inorganic chemicals have been added to polymeric materials to reflect NIR radiation, reducing heat inside the greenhouse, and absorbing UV radiation protecting the film from degradation. [4][5][6] However, organic substances have lower weather resistance and thermal stability than inorganic products.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] UV radiation affects film degradation and pollinators' behavior, and NIR radiation is a direct source of heat, which penetrates the greenhouses, excessively increasing the temperature, which is harmful to people who work inside and to the crops. [3] Thus, organic and inorganic chemicals have been added to polymeric materials to reflect NIR radiation, reducing heat inside the greenhouse, and absorbing UV radiation protecting the film from degradation. [4][5][6] However, organic substances have lower weather resistance and thermal stability than inorganic products.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] However, organic substances have lower weather resistance and thermal stability than inorganic products. [3] Among the inorganic substances, studies have shown that titanium dioxide nanoparticles have a high UV radiation absorption potential and boron nitride (BN) nanoplatelets have a high potential to reflect NIR. [5,6] One of the interesting properties of TiO 2 , when added to polymeric materials, is its ability to absorb UV radiation (λ < 400 nm), since polymer exposure to that radiation causes degradation and/or aging that affects their appearance (coloration) and their chemical and physical properties, for example.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this coated cover could repeatedly wash out by rain [9]. Recently, the greenhouse cover using silica as an addition to serve as a basis for radiation cooling was reported [10]. It was found that, under 35°C ambient conditions, the inside temperature of the simulated greenhouse with the 1% SiO 2 double layer films was 3 to 5°C less than that of the greenhouse with the commercial agricultural polyethylene (PE) film.…”
Section: Introductionmentioning
confidence: 99%
“…The greenhouse covering needs sunlight penetrating inside to keep the plants growing; therefore, it requires high transmittance in the visible radiation and high emissivity over the infrared atmosphere window. From past research, radiative cooling can be achieved by using some nonmetal oxide particle [7,10,[12][13][14][15][16][17]. Unlike the devices mentioned above, the covering of a greenhouse needs neither high reflection nor a complicated device so we only added nonmetal oxide particles as the base of films for radiation cooling rather than using complex composition.…”
Section: Introductionmentioning
confidence: 99%